Chapter Суффиксация как средство образования видовых пар в резьянском диалекте: славянская и иноязычная лексика - Benacchio, Rosanna (Biblioteca di Studi Slavistici, 2018)
In the paper morphological processes for creating aspectual pairs in Resian are discussed. A distinction is made between original Slavic verbs and verbs originating from other languages. In the former case the most productive process is prefixation (and perfectivation), whereas in the latter case for verbs of Romance origin the most productive process is suffixation (and imperfectivation). Verbs of Germanic origin also allow prefixation.